Performing Ploutos: Explorations into the religious discourse of 4th century Athens - Wagener, Isabell (ARYS. Antigüedad: Religiones y Sociedades, 2021)
The question of the relation of ritual and theatre has long been debated and may never come to a satisfying result. Nevertheless, certain features of theatrical performances, especially in the ancient Greek poleis, show a close connection of both performative acts. In particular, there is a strong interdependence of the dramatic agon and religious festivals, such as the Great Dionysia and the Lenaia. The aim of this article is to shed a new light not only on the relation of theatre and ritual, but also on the reception of theatre in the visual arts and the impact it had on religious developments of that time. I hereby focus on the heightened emergence of personifications in the middle of the 5th century BC which is reflected in a number of personifications who appear on stage in the Aristophanic comedies. One of them is Ploutos, the personified Wealth and one of the main characters in the homonymous play. By combining the representation of Ploutos in the visual arts with the literary sources on his person, a new image of this personification emerges. Through recapturing fragments and fractures of the multifaceted personification Ploutos, a process of transformation and adaption shows through that accommodates not only the relation of ritual and theatre, but also highlights the extraordinary standing of personification in the ancient Greek pantheon.
Keywords: mysteries; old comedy; performance; personification; ritual; visual arts; wealth